2013
DOI: 10.1021/jp4036666
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Characterization of the Molecular Conformation in Disordered Methyl α-l-Rhamnofuranoside

Abstract: Abstract.A combination of solid-state 13 C NMR tensor data and DFT computational methods are utilized to predict conformation in disordered methyl α-Lrhamnofuranoside. This previously uncharacterized solid is found to be crystalline and consists of at least six distinct conformations that exchange on the kHz timescale. A total of 66 model structures were evaluated and six were identified as being consistent with and is slow enough to be observed on the NMR timescale due to severe steric crowding among ring sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…As shown in Figure 28, 13 C relaxation measurements showed that both rings exhibited the same, small-angle libration-type motion, and re-fitting of the XRD data showed that the modelling of the diffraction data was fundamentally ambiguous. In the case of methyl α-L-rhamnofuranoside, the disorder in the structure was readily established to be dynamic by NMR, involving rates on the order of kHz, and slow enough to see multiple peaks per carbon site [367]. 66 molecular conformations were considered and the agreement of 13 C NMR shift tensor principal components assessed.…”
Section: Nmr Crystallography Of Disordered Materialsmentioning
confidence: 99%
“…As shown in Figure 28, 13 C relaxation measurements showed that both rings exhibited the same, small-angle libration-type motion, and re-fitting of the XRD data showed that the modelling of the diffraction data was fundamentally ambiguous. In the case of methyl α-L-rhamnofuranoside, the disorder in the structure was readily established to be dynamic by NMR, involving rates on the order of kHz, and slow enough to see multiple peaks per carbon site [367]. 66 molecular conformations were considered and the agreement of 13 C NMR shift tensor principal components assessed.…”
Section: Nmr Crystallography Of Disordered Materialsmentioning
confidence: 99%
“…While the FIREMAT methodh as not yet been appliedt oal arger protein, it is notable that this technique readily provides tensors for dozens of sites in as ingle experiment. [49,64,65] We therefore anticipate that FIREMAT-SPINAL will provide the resolution needed to study 15 Na mide sites in moderately sized proteins. [10] Several other FIREMATs tudies have characterized 34 or more 13 Cs ites in as ingle experiment.…”
Section: Evaluating the Accuracy Of Firemat-spinal At Two Spinning Spmentioning
confidence: 99%
“…[10] Several other FIREMATs tudies have characterized 34 or more 13 Cs ites in as ingle experiment. [49,64,65] We therefore anticipate that FIREMAT-SPINAL will provide the resolution needed to study 15 Na mide sites in moderately sized proteins.…”
Section: Evaluating the Accuracy Of Firemat-spinal At Two Spinning Spmentioning
confidence: 99%
“…13,14,28 Careful treatment of finite-temperature nuclear dynamics can also be important, even in the solid state. 15,4048 Here we focus on a different strategy: can we increase discrimination among distinct crystallographic environments by improving the accuracy of the chemical shift prediction?…”
Section: Introductionmentioning
confidence: 99%